Divalent regulation and intersubunit interactions of human Connexin26 (Cx26) hemichannels - Lopez, William (Landes Bioscience, 2014)
Control of plasma membrane connexin hemichannel opening is indispensable, and is achieved by physiological extracellular divalent ion concentrations. Here, we explore the differences between regulation by Ca(2+) and Mg(2+) of human connexin26 (hCx26) hemichannels and the role of a specific interaction in regulation by Ca(2+). To effect hemichannel closure, the apparent affinity of Ca(2+) (0.33 mM) is higher than for Mg(2+) (1.8 mM). Hemichannel closure is accelerated by physiological Ca(2+) concentrations, but non-physiological concentrations of extracellular Mg(2+) are required for this effect. Our recent report provided evidence that extracellular Ca(2+) facilitates hCx26 hemichannel closing by disrupting a salt bridge interaction between positions D50 and K61 that stabilizes the open state. New evidence from mutant cycle analysis indicates that D50 also interacts with Q48. We find that the D50-Q48 interaction contributes to stabilization of the open state, but that it is relatively insensitive to disruption by extracellular Ca(2+) compared with the D50-K61 interaction.